ChemInform Abstract: Ab initio Structure Determination and Photoluminescent Properties of an Efficient, Thermally Stable Blue Phosphor, Ba2Y5B5O17:Ce3+. Issue 18 (April 2016) - Hermus, Martin; Phan, Phu‐Cuong; Brgoch, Jakoah
Abstract: Ba2 Y5 B5 O17 and Ba2 (Y4.75 Ce0.25 )B5 O17 are prepared by firing stoichiometric amounts of BaCO3, Y2 O3 (and CeO2 ), and H3 BO3 under a 5% H2 /N2 reducing atmosphere (Al2 O3 crucible, 1200 °C, 24 h).